Student performance and perceptions in a hybrid laboratory model: an exploratory study of interactive virtual simulations and in-person integration in a foundational microbiology course - Vanessa Ayer Miller; Timothy Marks; Dorothea K. Thompson (Journal of Microbiology & Biology Education, 2025)
ABSTRACT Interest in virtual laboratory simulations as a pedagogical tool continues to grow, given the advantages of flexibility, scalability, technology integration, and interactive visualizations. We developed a laboratory model that integrates virtual lab simulations (VLS) and traditional in-person (IP) lab experiences for targeted skill development. In this study, we aimed to compare the effectiveness of VLS versus IP labs in the promotion of procedural, conceptual, and critical thinking levels of understanding. A second research objective was to explore students’ perceptions in using VLS compared to IP labs in an undergraduate microbiology course. Study participants comprised students (n = 49) enrolled in a foundational microbiology course at a private university in the Fall semesters of 2022 and 2023. Identical quizzes were administered to assess learning performance of students who received the VLS first and those who completed the IP lab first. Focus group discussions were conducted, and participant responses were audio recorded for accuracy purposes, transcribed, and analyzed thematically using open and axial coding. The results indicated differences in performance scores between the VLS and IP groups were not statistically significant, suggesting both lab modalities are effective in enhancing learning. Overall, students expressed positive perceptions of VLS, noting detailed explanations, repetition, time management, and visual learning as primary benefits. Furthermore, students indicated an interest in using VLS in a hybrid structure as either a pre-laboratory exercise or a supplemental lab. These findings support the utility of a hybrid laboratory model in a foundational microbiology course for training pre-clinical students.